2009
DOI: 10.1093/schbul/sbn178
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Hedonic Judgment in Patients With Deficit Syndrome Schizophrenia

Abstract: Olfactory perception was examined in deficit syndrome (DS) and nondeficit syndrome (ND) schizophrenia patients. Participants included 22 controls (CN) and 41 patients with schizophrenia who were divided into DS (n = 15) and ND (n = 26) subtypes using the Schedule for the Deficit Syndrome (SDS). Olfactory perception for pleasant and unpleasant odors was assessed using the Brief Smell Identification Test. Participants were instructed to identifying each smell as well as provide hedonic judgment ratings of each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
4
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 44 publications
5
46
4
3
Order By: Relevance
“…Kayser et al, 2013;Turetsky et al, 2008), allow sensory information to reach orbitofrontal regions (Brewer et al, 2006). This hypothesis is supported by the findings that OI deficits are associated with negative symptoms (Brewer et al, 1996a(Brewer et al, , 2001Corcoran et al, 2005;Good et al, 2006;Ishizuka et al, 2010) and more specifically, the deficit syndrome of schizophrenia (Strauss et al, 2010).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Kayser et al, 2013;Turetsky et al, 2008), allow sensory information to reach orbitofrontal regions (Brewer et al, 2006). This hypothesis is supported by the findings that OI deficits are associated with negative symptoms (Brewer et al, 1996a(Brewer et al, , 2001Corcoran et al, 2005;Good et al, 2006;Ishizuka et al, 2010) and more specifically, the deficit syndrome of schizophrenia (Strauss et al, 2010).…”
Section: Introductionmentioning
confidence: 76%
“…In that study, OI deficits appear to be most strongly related to overall social and occupational functioning, and specifically to maintaining employment and meeting basic needs. Furthermore, Strauss et al (2010) reported reduced olfactory hedonic judgement in the deficit syndrome diagnostic subtype, along with a negative relationship between negative symptom severity and OI ability. However, in the current study, no relationship between OI and negative symptoms was found in any group.…”
Section: Discussionmentioning
confidence: 99%
“…Both the SCID and PANSS were administered by experienced and clinically trained psychologists. Of the patients, 22 were taking atypical neuroleptics, 1 was taking both typical and atypical medication and 1 was unmedicated. Eight patients were receiving serotonin reuptake inhibitors in addition to neuroleptic treatment.…”
Section: Participantsmentioning
confidence: 99%
“…21 This is despite the fact that an increasing body of research reports that patients show declarative deficits in olfactory functioning, affecting identification and hedonic judgment. [22][23][24] The aim of our study was to investigate whether crossmodal effects between olfactory and visual stimuli are impaired in patients with schizophrenia compared with healthy controls. We expected that, in line with previous studies, 10 the odorants would influence the perception of emotional faces in the healthy participant group.…”
Section: Introductionmentioning
confidence: 99%
“…Tests were administered as part of a larger battery that included other neuropsychological measures, computerized tests, and clinical interviews (Duke et al, 2010;Strauss and Allen, 2013;Strauss et al, 2008Strauss et al, , 2010aStrauss et al, , 2011Strauss et al, , 2010bStrauss et al, , 2012Vogel et al, 2013). Diagnostic and symptom interviews occurred prior to neuropsychological testing.…”
Section: Methodsmentioning
confidence: 99%